An experimental method to estimate the temperature of individual nanowires. (25th June 2009) - Prades, J.D.; Jimenez-Diaz, R.; Hernandez-Ramirez, F.; Barth, S.; Pan, J.; Cirera, A.; Romano-Rodriguez, A.; Mathur, S.; Morante, J.R.
In this paper, the authors present an effective experimental method to estimate the temperature of individual metal oxide nanowires that can be used to quantify the heating produced in conductometric or other operating conditions. The here-proposed method is based on the analysis of the recovery time of the nanowire's resistance after exposure to a gas pulse (0.5 ppm of NO2 in dry air). It is reproducible with different devices always with uncertainties below ±20°C in the temperature range (70-300°C) studied herein. The exploration of alternative gases and nanolithography techniques may help to extend its operating range and its applicability to other materials. In any case, the opportunity to probe temperatures at the nanoscale opens the door to a number of fundamental and applied advancements in the field of nanotechnology.